Applications of a hyper-graph grammar system in adaptive finite-element computations - Gurgul, Piotr; Jopek, Konrad; Pingali, Keshav; Paszyńska, Anna (Zielona Góra: Uniwersytet Zielonogórski)
This paper describes application of a hyper-graph grammar system for modeling a three-dimensional adaptive finite element method. The hyper-graph grammar approach allows obtaining a linear computational cost of adaptive mesh transformations and computations performed over refined meshes. The computations are done by a hyper-graph grammar driven algorithm applicable to three-dimensional problems. For the case of typical refinements performed towards a point or an edge, the algorithm yields linear computational cost with respect to the mesh nodes for its sequential execution and logarithmic cost for its parallel execution.
Keywords: adaptive finite element method; hyper-graph grammars; mesh-based computations